A Template Of Scientific Application In The Islamic World: Advent Of Agriculture In Saudi Arabia (Journal of Namibian Studies : History Politics Culture, 2023)
The paper explores a survey of texts as well as physical surveys in Saudi Arabia to establish the importance that the Islamic culture places on scientific and technological development, along with preserving traditions and culture. This has led them to become reasonably large producers of food grains, fruits, vegetables as well as horticultural plants. Also, industries around this produce have also been encouraged. The political turmoils of the region notwithstanding, the Islamic people are part of the great human endeavour of life.